Modulating patterned adhesion and repulsion of HEK 293 cells on microengineered parylene-C/SiO(2) substrates - Hughes, M. A. (J Biomed Mater Res A, 2012)
This article describes high resolution patterning of HEK 293 cells on a construct of micropatterned parylene-C and silicon dioxide. Photolithographic patterning of parylene-C on silicon dioxide is an established and consistent process. Activation of patterns by immersion in serum has previously enabled patterning of murine hippocampal neurons and glia, as well as the human hNT cell line. Adapting this protocol we now illustrate high resolution patterning of the HEK 293 cell line. We explore hypotheses that patterning is mediated by transmembrane integrin interactions with differentially absorbed serum proteins, and also by etching the surface substrate with piranha solution. Using rationalized protein activation solutions in place of serum, we show that cell patterning can be modulated or even inverted. These cell-patterning findings assist our wider goal of engineering and interfacing functional neuronal networks via a silicon semiconductor platform.